The therapy frequency of antibiotics and phenotypical resistance of Escherichia coli in calf rearing sites in Germany - Merle, Roswitha; Weise, Susann; Gorisek, Lisa; Baer, Jorinde; Robé, Caroline; Friese, Anika; Jensen, Katharina Charlotte (Frontiers in Veterinary Science, 2023)
The association between antibiotic use and the occurrence of resistant bacteria is a global health problem and is subject to enormous efforts at national and international levels. Within the scope of the study "KAbMon,”, the resistance situation as well as the use of antibiotics in calf rearing farms in Germany was investigated. We hypothesized that the levels of resistance are associated with certain calf keeping farm types, such as pre-weaned calf farms, animal groups, and therapy frequency. In total, 95 calf keeping farms were visited between October 2019 and April 2021. At each farm, up to three pooled fecal samples (10 freshly released feces each) were collected. One sample was taken in the youngest calf group, another in the oldest calf group, and one in the hospital box, if available. Escherichia coli was isolated from non-selective MacConkey agar. The therapy frequency reflects the average number of treatment days per calf in a half-year, while the resistance score is the sum of the relative minimum inhibitory concentration per substance over all 10 tested substances. The 1781 isolates from 178 samples showed high resistance rates against sulfamethoxazole (82%), tetracycline (49%), and ampicillin (40%). High resistance scores were mainly found in pre-weaned calf farms (purchasing calves from 2 weeks of life) and in the youngest animals. The therapy frequency showed an almost linear relationship with the resistance scores, and the age at purchase was negatively related to the resistance score. This showsThe high use of antimicrobials of young calves might be associated with a high that mainly the young calves are of highest risk for infectious diseases and might indicate that the current system of crowding 14-day-old calves from different farms in one group is not optimal. Further efforts are necessary to educate and motivate the calf keepers to ensure highest levels of hygiene and management as well as animal welfare conditions and to increase animal health.